2012
DOI: 10.1021/jp2120143
|View full text |Cite
|
Sign up to set email alerts
|

Combining Statistical Potentials with Dynamics-Based Entropies Improves Selection from Protein Decoys and Docking Poses

Abstract: Protein structure prediction and protein-protein docking are important and widely used tools, but methods to confidently evaluate the quality of a predicted structure or binding pose have had limited success. Typically, either knowledge-based or physics-based energy functions are employed to evaluate a set of predicted structures (termed "decoys" in structure prediction and "poses" in docking), with the lowest energy structure being assumed to be the one closest to the native state. While successful for many c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 59 publications
0
35
0
Order By: Relevance
“…The potential energy of each structure was estimated as an optimized linear combination of three different knowledge-based potential terms that we previously developed: four-body sequential potential, four-body nonsequential potential, and short-range potentials (50)(51)(52)(53). The potential energy was calculated as V opt = V 4−body seq + 0.28 * V 4−body non−seq + 0.22 * V short range .…”
Section: Methodsmentioning
confidence: 99%
“…The potential energy of each structure was estimated as an optimized linear combination of three different knowledge-based potential terms that we previously developed: four-body sequential potential, four-body nonsequential potential, and short-range potentials (50)(51)(52)(53). The potential energy was calculated as V opt = V 4−body seq + 0.28 * V 4−body non−seq + 0.22 * V short range .…”
Section: Methodsmentioning
confidence: 99%
“…A more detailed review of various methods of entropy estimation can be found in Meirovitch et al (10). Recently, we have shown that by combining statistical potentials with entropy measures obtained from coarse-grained elastic network models (ENMs), an improvement can be achieved, especially in discriminating native protein-protein complexes from docked poses, reflecting the largest scale changes in dynamics (31,32). This result is based on previous findings that large-scale changes to the dynamics accompany bound states.…”
Section: Significancementioning
confidence: 99%
“…One might assume that implicit solvent models would have overcome this limitation of explicit monopole models of water; unfortunately, they have been calibrated primarily with results from explicit calculations with monopole force fields. One can understand the rise in popularity of statistically based potentials derived from experimental atomic proximities that inherently avoid energetic dichotomies and focus on free energy per se [36,37]. …”
Section: Monopole Versus Multipole Electrostaticsmentioning
confidence: 99%